Neural stem cells and oligodendrocyte progenitor cells compete for remyelination in the corpus callosum - Moyon, Sarah; Holloman, Mara; Salzer, James L. (Frontiers in Cellular Neuroscience, 2023)
A major therapeutic goal in demyelinating diseases, such as Multiple Sclerosis, is to improve remyelination, thereby restoring effective axon conduction and preventing neurodegeneration. In the adult central nervous system (CNS), parenchymal oligodendrocyte progenitor cells (pOPCs) and, to a lesser extent, pre-existing oligodendrocytes (OLs) and oligodendrocytes generated from neural stem cells (NSCs) in the sub-ventricular zone (SVZ) are capable of forming new myelin sheaths. Due to their self-renewal capabilities and the ability of their progeny to migrate widely within the CNS, NSCs represent an additional source of remyelinating cells that may be targeted to supplement repair by pOPCs. However, in demyelinating disorders and disease models, the NSC contribution to myelin repair is modest and most evident in regions close to the SVZ. We hypothesized that NSC-derived cells may compete with OPCs to remyelinate the same axons, with pOPCs serving as the primary remyelinating cells due to their widespread distribution within the adult CNS, thereby limiting the contribution of NSC-progeny. Here, we have used a dual reporter, genetic fate mapping strategy, to characterize the contribution of pOPCs and NSC-derived OLs to remyelination after cuprizone-induced demyelination. We confirmed that, while pOPCs are the main remyelinating cells in the corpus callosum, NSC-derived cells are also activated and recruited to demyelinating lesions. Blocking pOPC differentiation genetically, resulted in a significant increase in the recruitment NSC-derived cells into the demyelinated corpus callosum and their differentiation into OLs. These results strongly suggest that pOPCs and NSC-progeny compete to repair white matter lesions. They underscore the potential significance of targeting NSCs to improve repair when the contribution of pOPCs is insufficient to affect full remyelination.